Coping with Toxic Leadership in the Academy: Perspectives on the Triple Threat to Faculty, Students and Community - Holmes; Parker; Willis (Advances in Social Sciences Research Journal, 2023)
Uncertain times, like widespread disruption from the coronavirus (COVID-19) pandemic, exacerbate existing organizational inequity and inefficiency. Evidence of this disparity exists in the leadership construct within academe. Toxic leadership is not a new concept in higher education, and it persists as a pitfall, jeopardizing the quality of educational programs, collaboration of faculty, and success of students. This paper utilized qualitative discourse analysis to examine the social context of ongoing dialogue among faculty members working to overcome the challenges of a new advanced degree program plagued by the lack of organizational capacity to respond to toxic leadership manifested during a global event affecting all of higher education around the world. The lived experience of faculty working with a new senior leader and the disruptive actions threatening to diminish the quality, sustainability and future success of a terminal degree program is the foundation of this paper.